Financial Determinants of Profitability in Post-Merger Islamic Banking: Evidence from Bank Syariah Indonesia (2020–2024) - Yasmin Zahira, Afifa; Sakdiah, Khairani (El-kahfi | Jurnal Ekonomi Islam, 2025)
The objective of study to determine the effect of Capital Adequacy Ratio, Financing to Deposit Ratio, and Non Performing Financing at PT Bank Syariah Indonesia. The type of research conducted was quantitative research which emphasizes numerical data (numbers) processed by inferential statistical methods (analyzing the relationship between variables by testing hypotheses). The data source of this research is obtained from secondary data, namely the quarterly financial statements of PT Bank Syariah Indonesia from 2020 to the second quarter of 2020 published on the website www.ojk.go.id. The results showed that: (1) Capital Adequacy Ratio has no effect on Return On Asset, (2) Financing to Deposit Ratio has a positive effect on Return On Asset, (3) Non Performing Financing has a negative effect on Return On Asset, (4) Capital Adequacy Ratio, Financing to Deposit Ratio, and Non Performing Financing jointly affect Return On Asset.